Early childhood psychopathology and parental mental health during the COVID-19 pandemic: the effects of pandemic restrictions on 0- to 3-year-olds - Keller, K.; Taubner, S.; Georg, A. K. (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction The COVID-19 pandemic placed many restrictions on families and affected the mental health of parents and children. The present study examines how the restrictions imposed during the pandemic and parental mental health affect early childhood psychopathology. Method From September 2019 to December 2021, the Outpatient Department of Family Therapy at the Institute for Psychosocial Prevention, Heidelberg surveyed a clinical sample of 249 families who sought consultation for early childhood psychopathology. Early childhood psychopathology in children aged 0–3 years was assessed using the German Questionnaire for Crying, Feeding and Sleeping and the German version of the Child Behavior Checklist 1½–5. The Patient Health Questionnaire provided information on parental depressiveness and generalized anxiety. At the same time, the Stringency Index as part of the Oxford Coronavirus Government Response Tracker indicated the severity of COVID restrictions in Germany. Results Dependent comparisons did not reveal significant differences in the infants' regulatory problems (n = 165, mean age = 8 months) during the lockdown compared to reopening phases. However, older children (n = 84, mean age = 25 months) exhibited more behavioral problems during lockdowns compared to reopening phases (Cohen's d = 0.32, p = .04). Subsequent regression analyses confirmed a slight increase in behavioral problems only among children aged 1.5–3 years (p = .047, R2 = .08), but did not indicate any increase in parental mental health problems when more restrictions were in place. However, parental depressiveness had a strong independent effect on early childhood psychopathology. A hierarchical regression analysis indicated that psychopathology in children aged 1.5–3 years is best explained by female child gender, high parental depressiveness, and more severe restrictions during the COVID-19 pandemic (p < .001, R2 = .17) whereas early childhood psychopathology in infants aged 0-1.5 years is more prevalent in younger and male children with parents experiencing higher levels of depressiveness (p < .001, R2 = .26). Discussion The study found no increase in infant regulatory disorders or parental depressiveness and generalized anxiety during the pandemic. However, older children exhibited more behavioral problems during more severe pandemic restrictions. The study supports the provision of parent-child support during crises and beyond, as early childhood psychopathology was strongly associated with parental depressiveness.